2020
DOI: 10.1155/2020/8679861
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Water–Sand Mixed Fluid Initiation and Migration in Porous Skeleton during Water and Sand Inrush

Abstract: Water–sand inrush is one of the most serious disasters for mining in China. The evaluation of the occurrence and development of a high-concentration water and sand mixed fluid is an important issue for mining in China. In this study, contraposing to the 3 phases of water–sand inrush, three kinds of experiments are designed for the investigation of initiation, development, and occurrence of the disaster. A new sand–water transport testing system is setup to perform the tests. The results show that there are two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…For the research on the motion properties of two-phase flow, the results show that the threshold velocity of the motion of the particles is affected by their sizes (Yang et al 2020;Zhang et al 2021a). Considering the aggregation effect of particles under the interparticle adhesion, Wang et al (2019b) simplified the fractured sand-stone samples.…”
Section: Modelling and Numerical Studymentioning
confidence: 99%
“…For the research on the motion properties of two-phase flow, the results show that the threshold velocity of the motion of the particles is affected by their sizes (Yang et al 2020;Zhang et al 2021a). Considering the aggregation effect of particles under the interparticle adhesion, Wang et al (2019b) simplified the fractured sand-stone samples.…”
Section: Modelling and Numerical Studymentioning
confidence: 99%
“…Ma et al [40] indicated that this behaviour may be related with the rearrangement of the skeleton. By conducting numerous experimental studies, Yang et al [44] concluded that, at the beginning of the test, water is the dominant phase. As the water flow velocity However, this may be related to the rheological properties of the mixed fluid, because extremely small changes in the concentration of aeolian sand can lead to large variations in velocity [45].…”
Section: Water-sand Two-phase Migration Characteristicsmentioning
confidence: 99%
“…Abundant coal resources (36% of coal resources) are found in the western region of China; however, it is prone to have water and sand inrush disasters in the mining process due to the fragile ecological environment in the western region [1][2][3]. As presented in Figure 1 [4], the broken rock mass (porous skeleton) in the caving zone connects the aquifer and the goaf zone during the mining process, constituting an effective channel for the transport of water-sand mixed fluids [5,6].…”
Section: Introductionmentioning
confidence: 99%